1997
DOI: 10.1007/bf02050426
|View full text |Cite
|
Sign up to set email alerts
|

Use of epidural anesthesia and spontaneous ventilation during transabdominal colon and rectal procedures in selected high-risk patient groups

Abstract: Use of epidural anesthesia with spontaneous ventilation in elective transabdominal colon and rectal procedures may decrease the incidence of pulmonary complications and length of postoperative hospital stay in a select group of high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…The application of postoperative epidural analgesia may be associated with the following benefits vis‐ à ‐vis systemic PCA: improved quality of analgesia, shortening of the duration of postoperative ileus with improvement of the perfusion of the splanchnic bed, better vigilance, and a reduction in the thromboembolism rate. Whether there is an associated reduction in morbidity and mortality rates has at present not been established [4244].…”
Section: Discussionmentioning
confidence: 99%
“…The application of postoperative epidural analgesia may be associated with the following benefits vis‐ à ‐vis systemic PCA: improved quality of analgesia, shortening of the duration of postoperative ileus with improvement of the perfusion of the splanchnic bed, better vigilance, and a reduction in the thromboembolism rate. Whether there is an associated reduction in morbidity and mortality rates has at present not been established [4244].…”
Section: Discussionmentioning
confidence: 99%
“…Mehrere Publikationen kamen damals zu dem Ergebnis, dass die Periduralanästhesie die Erholung nach gastrointestinalen Eingriffen beschleunigt [11,12,13]. Sie sei mit einer verkürzten postoperativen Darmparalyse [11,12], mit einer Dämpfung der Stressantwort [14], einer Reduktion pulmonaler Komplikationen [13,15] und natürlich verbesserter Schmerzkontrolle assoziiert [11,12]. Die Analgesie mittels PDK wurde somit schnell zum integralen Bestandteil von Fast-Track-Konzepten.…”
Section: Periduralkatheter (Pdk)unclassified
“…Als gute Alternative etablierte sich um die Jahrtausendwende die Analgesie mittels Periduralkatheter (PDK). Mehrere Publikationen kamen damals zu dem Ergebnis, dass die Periduralanästhesie die Erholung nach gastrointestinalen Eingriffen beschleunigt [11,12,13]. Sie sei mit einer verkürzten postoperativen Darmparalyse [11,12], mit einer Dämpfung der Stressantwort [14], einer Reduktion pulmonaler Komplikationen [13,15] und natürlich verbesserter Schmerzkontrolle assoziiert [11,12].…”
Section: Periduralkatheter (Pdk)unclassified
“…Epidural analgesia in spontaneously breathing high‐risk patients (those with an American Society of Anesthesiologists physical status of III or more) reduces pulmonary complications115 and in patients with limited pulmonary reserve the duration of postoperative mechanical ventilation90. A meta‐analysis of randomized clinical trials relating method of analgesia to pulmonary outcome concluded that epidural opioid reduced pulmonary atelectasis and, to a lesser extent, infection, whereas epidural local anaesthetic increased arterial oxygen saturation and decreased the risk of pulmonary infection107.…”
Section: Other Intraoperative Effects Of Epidural Analgesiamentioning
confidence: 99%
“…Despite the benefits outlined above, studies have not demonstrated a shorter hospital stay ( Table 5 ) or reduction in hospital costs36 with epidural analgesia, although there is an epidural‐related reduction in length of stay82, 110, 115 and cost82, 83, 115 in patients at high risk of cardiopulmonary complications. Epidural analgesia during and for 48 h after surgery, with an intensive and standardized nursing regimen involving early feeding and mobilization, has been reported to decrease hospital stay after sigmoid colectomy to a median of 2 days3.…”
Section: Influence Of Epidural Analgesia On Recovery and Hospital Staymentioning
confidence: 99%